Morbidity and Mortality Following Total Hip Replacement in Dogs - Liska, William D.; Israel, Sarah K. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective The objective of this study was to determine morbidity and mortality rates in dogs that had undergone a total hip replacement surgery with implantation of either a cemented or a cementless prosthesis (BioMedtrix LLC, Whippany, NJ).Methods The survival time after surgery, the date of death and the cause of death were collated from an ongoing registry maintained on consecutive total hip replacement procedures by a single surgeon.Results A review of the 1,864 dogs entered in the total hip replacement registry revealed 642 in which the date of death and cause of death were known. The mean life span of the dogs in this study was 11.3 years, with the longest being 17.1 years. The mean survival after total hip replacement was 4.66 years, with the longest being 16.1 years. Multiorgan system failure was more common than any single organ system failure. The most common pathophysiological process leading to death was neoplasia.Clinical Significance Morbidity and mortality rates are helpful for surgeons to compare outcomes and to inform animal owners about anaesthesia and procedural risks when contemplating this surgery. This information can be used for a better understanding of expectations for a dog's health after total hip replacement surgery.
Keywords: total hip replacement; morbidity; mortality; dog; canine; multiorgan system failure